Mesothelin Expression in Gastric Adenocarcinoma and Its Relation to Clinical Outcomes - Song-Hee Han; Mee Joo; Hanseong Kim; Sunhee Chang (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Background Although surgical resection with chemotherapy is considered effective for patients with advanced gastric cancer, it remains the third leading cause of cancer-related death in South Korea. Several studies have reported that mesothelial markers including mesothelin, calretinin, and Wilms tumor protein 1 (WT1) were positive in variable carcinomas, associated with prognosis, and were evaluated as potential markers for targeted therapy. The aim of this study was to assess the immunohistochemical expression of mesothelial markers (mesothelin, calretinin, and WT1) in gastric adenocarcinoma and their relations to clinocopathological features and prognosis. Methods We evaluated calretinin, WT1, and mesothelin expression by immunohistochemical staining in 117 gastric adenocarcinomas. Results Mesothelin was positively stained in 30 cases (25.6%). Mesothelin expression was related to increased depth of invasion (p = .002), lymph node metastasis (p = .013), and presence of lymphovascular (p = .015) and perineural invasion (p = .004). Patients with mesothelin expression had significantly worse disease-free survival rate compared with that of nonmesothelin expression group (p = .024). Univariate analysis showed that mesothelin expression is related to short-term survival. None of the 117 gastric adenocarcinomas stained for calretinin or WT1. Conclusions Mesothelin expression was associated with poor prognosis. Our results suggest that mesothelin-targeted therapy should be considered as an important therapeutic alternative for gastric adenocarcinoma patients with mesothelin expression.